Relative frequency of non‐Hodgkin lymphoma subtypes in selected centres in North Africa, the middle east and India: a review of 971 cases. (18th December 2015) - Perry, Anamarija M.; Diebold, Jacques; Nathwani, Bharat N.; MacLennan, Kenneth A.; Müller‐Hermelink, Hans K.; Bast, Martin; Boilesen, Eugene; Armitage, James O.; Weisenburger, Dennis D.
Summary: Comparative data regarding the distribution of non‐Hodgkin lymphoma (NHL) subtypes in North Africa, the Middle East and India (NAF/ME/IN) is scarce in the literature. In this study, we evaluated the relative frequencies of NHL subtypes in this region. Five expert haematopathologists classified 971 consecutive cases of newly‐diagnosed NHL from five countries in NAF/ME/IN. After review, 890 cases (91·7%) were confirmed to be NHL and compared to 399 cases from North America (NA). The male‐to‐female ratio was significantly higher in NAF/ME/IN (1·8) compared to NA (1·1; P < 0·05). The median ages of patients with low‐grade (LG) and high‐grade (HG) B‐NHL in NAF/ME/IN (56 and 52 years, respectively) were significantly lower than in NA (64 and 68 years, respectively). In NAF/ME/IN, a significantly lower proportion of LG B‐NHL (28·4%) and a higher proportion of HG B‐NHL (58·4%) were found compared to NA (56·1% and 34·3%, respectively). Diffuse large B‐cell lymphoma was more common in NAF/ME/IN (49·4%) compared to NA (29·3%), whereas follicular lymphoma was less common in NAF/ME/IN (12·4%) than in NA (33·6%). In conclusion, we found significant differences in NHL subtypes and clinical features between NAF/ME/IN and NA. Epidemiological studies are needed to better understand the pathobiology of these differences.